A Review of Primate Research and Conservation in Sarawak, Malaysia - Nur Aizatul, Tukiman; Noor Faezah, Mohammad; Roberta Chaya Tawie, Tingga; Bukhori, Mohamad Fhaizal; Mohd Azlan, Jayasilan; Denel, Azroie; Md Zain, Badrul Munir; Abdul Latiff, Muhammad Abu Bakar; Mohd Ridwan, Abd Rahman (Arak University, 2023)
Sarawak is home to a diverse array of primate species in Malaysia, i.e., 14 species from five families. Over the years, many studies on primates’ behavior, ecology and conservation have been conducted in Sarawak. Here, we provide a comprehensive overview of previous primate studies in Sarawak from 1960 to 2022 and discuss primates' threats, conservation status, and initiatives. Despite the vast number of these primate studies, the majority of them only focus on proboscis monkeys (n=24) and orangutans (n=21) and lack comprehensive studies that cover all primate species in Sarawak. Studies on ecology and natural history were the most prevalent for all Sarawak primate genera (n=51), accounting for more than half of publications. Thus, it advocates a more holistic approach to fill the knowledge gaps and meet conservation needs. Conservation efforts are urgently needed to protect primates currently threatened by deforestation, habitat fragmentation, hunting, and illegal trade. However, conservation efforts may be restrained by the limited information on primates in Sarawak. To preserve the primates in Sarawak, a robust protection strategy that synergizes the participation of government authorities, non-government organizations, and local communities needs to be developed